Lanthanoids and transition metals saturable absorber film for short pulse fiber laser generation at 1.0 and 1.55 micron Region / Mohamad Faizal Baharom - Mohamad Faizal , Baharom (2021)
As pulsed laser technology has found expanding application in material processing, telecommunications, medical diagnostics and numerous other areas, the desire for inexpensive and robust laser sources has grown. Until recently, various passive saturable absorbers (SAs) have been introduced in developing Q-switched and mode-locked fiber lasers. However, tremendous research effort has been devoted to searching new alternative SA materials which accompany with high operation performance and simple SA fabrication method. This thesis proposed and demonstrated novel SA devices based on lanthanoid and metal oxides for developing various Q-switched and mode-locked fiber lasers operating at ~1 and 1.5 μm regions. New passive SAs based on three different materials: vanadium pentoxide (V2O5), lutetium oxide (Lu2O3) and nickel oxide (NiO) have been successfully fabricated and characterized in this work. V2O5 and NiO materials were embedded into polyethylene glycol (PEG) while Lu2O3 was embedded into polyvinyl alcohol (PVA) to compose a film absorber, which was then sandwiched between two fiber ferrule connectors with a fiber adapter to form a fiber compatible SA. The V2O5, Lu2O3 and NiO based SA has a modulation depth of 7 %, 10 % and 9%, respectively. Various Q-switched and mode-locked fiber lasers have been successfully demonstrated in both 1- and 1.5- micron regimes by using the newly developed SAs in both 1- and 1.5-micron regimes. For instance, a Q-switched YDFL operating at 1067.8 nm was demonstrated using the Lu2O3 SA. The laser generates a stable pulses train with a pump power range from 116 mW to 151 mW with the maximum repetition rate of 46.68 kHz, the shortest pulse width of 4.6 μs and the highest pulse energy of 128 nJ. A soliton mode-locked Erbium-doped fiber laser (EDFL) operating at 1561.4 nm with a pulse width as short as 710 fs was also successfully realized using the NiO based SA by optimizing the cavity design to operate at anomalous cavity dispersion of -0.282 ps2.